Investigating Teacher’s Code- Switching in English Pedagogical Process - Jihan Rizkika Chairunisa; Setyo Wati; Wida Mulyanti (Journal of Applied Linguistics (ALTICS), 2024)
This study deals with the phenomenon of code-switching in the English pedagogical process. Code-switching naturally occurs in bilingual or EFL teaching since each student has a distinct linguistic background. This research aims to analyze the types of code-switching and explore the English teacher's purposes for using code-switching in the teaching English process in the eighth grade of SMP Al-Muttaqin. This research employed a phenomenological case study that focuses on a single case and single subject of an English teacher with a triangulation of data. The data were observation, interview, and an open-ended questionnaire to understand and reveal the process of the teacher's code-switching phenomenon through in-depth analysis for almost a month in August 2022. The findings revealed that the teacher employed code-switching depending on the situation and condition of the students. There were three types of code-switching used by the English teacher. The number of tag switching type was 117, such as used by the teacher in affective function. The number of intra-sentential type was 33, such as used by the teacher in the topic switch and the number of inter-sentential type was 189, commonly used by the teacher in repetition for clearer understanding in clarifying the meaning.